Changed expression of placental transporters and disrupted epigenetic patterns in a rat model of schizophrenia - Szatmári, Péter; Seres-Bokor, Adrienn; Sztojkov-Ivanov, Anita; Kékesi, Gabriella; Horváth, Gyöngyi; Ducza, Eszter (Frontiers in Pharmacology, 2025)
IntroductionGenerally, the pregnant women with schizophrenia have higher consumption of medicinal drugs. During pregnancy, placental ABC transporters regulate drug disposition and are involved in fetal and placental development. This study examined the expression and function of placental P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) transporters in vivo and evaluated the epigenetic impact of schizophrenia on the placenta in a rat model.MethodsThe expression of placental P-gp and BCRP was measured by RT-PCR and Western blot techniques in schizophrenia-like Wisket and control Wistar rats on gestation days 15, 18, 20, 21, and 22, while the histone acetyltransferase activity and global methylation state of the placenta were detected by colorimetric kits. Fexofenadine was administered per os (10 mg/kg) to pregnant rats and plasma concentrations of fexofenadine were determined with HPLC analysis on the 21 and 22 days of gestation.ResultsReduced placental P-gp expression was identified in late pregnancy, while the placental BCRP expression upregulation was observed before term in schizophrenia. Significantly lower fetal fexofenadine plasma concentration was measured on the 21st and 22nd days of pregnancy compared to the mother; in contrast, the fexofenadine concentration was similar in the schizophrenia-like mother and fetus. Decreased placental histone acetyltransferase activity and DNA hypermethylation were revealed before term in schizophrenia-like rats.ConclusionBased on our results, we can conclude that the expression and function of the placental efflux proteins we examined are altered in schizophrenia, and possibly as a result, altered substrate concentrations were measured in the fetuses. We hypothesize that the altered protein expression may also be a result of the disease-induced epigenetic pattern changes. This study presents novel disease-associated placental ABC transporter alterations, which highlights the dangers of using transporter substrates, especially P-gp, during pregnancy.